Critical Review of Almudena Grandes’s «Las edades de Lulú»: For a New Reading as a Bildungsroman (Castilla. Estudios de Literatura, 2019)
Las edades de Lulú (1989), Almudena Grandes’s first novel, was also one of the first works in her literary career to catch the attention of the academia. Mostly, critics have been concerned with the question of gender, and, although there have been mentions to the narrative nature of the novel as a Bildungsroman, this has usually been cornered by the debate on the sexist or feminist issues contained in the plot. This article re-examines this debate in the light of Almudena Grandes’s ideas on literature and her own opinions on Las edades de Lulú. In addition, it offers a new reading of the novel as a Bildungsroman, focusing on its narrative techniques and comparing it with the remote model of the picaresque and, particularly, Lazarillo de Tormes. This analysis allows for a more rigorous debate on gender in the novel, for it parts closely from the text itself.
Keywords: Almudena Grandes; Las edades de Lulú; Bildungsroman; Lazarillo de Tormes; gender studies